2022
DOI: 10.1161/strokeaha.121.037980
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Extracranial Internal Carotid Artery Disease in Children With Sickle Cell Anemia

Abstract: Background: Cerebral arteriopathy in patients with sickle cell anemia mainly affects the intracranial anterior circulation. However, the extracranial internal carotid artery (eICA) can also be stenosed and responsible for ischemic lesions. In children with sickle cell anemia, we perform routine annual Doppler ultrasound assessment of the eICA and magnetic resonance imaging with 3-dimensional time-of-flight magnetic resonance angiography of the Willis circle and neck arteries in those with abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Thus, the authors suggested that systematic detection of extracranial stenosis may have limited clinical utility in patients with SCD ( 27 ). However, Verlhac et al ( 28 ) recently reported in the Debré, Paris, cohort the presence of eICA stenosis in 48 children with SCA, of whom eight had a history of stroke; importantly, five of eight had isolated eICA stenosis, confirming the clinical utility to systematically assess the extracranial part of the internal carotid artery.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the authors suggested that systematic detection of extracranial stenosis may have limited clinical utility in patients with SCD ( 27 ). However, Verlhac et al ( 28 ) recently reported in the Debré, Paris, cohort the presence of eICA stenosis in 48 children with SCA, of whom eight had a history of stroke; importantly, five of eight had isolated eICA stenosis, confirming the clinical utility to systematically assess the extracranial part of the internal carotid artery.…”
Section: Discussionmentioning
confidence: 90%
“…Overt stroke is mainly related to chronic stenosis and occlusion of large cerebral arteries in the anterior circulation resulting from intimal thickening 4,5 , described as cerebral arteriopathy related to SCD (SCD-CA). The internal carotid, including its extracranial part 6 , middle cerebral, and anterior cerebral arteries are often involved in ischemic stroke 7,8 and up to 71% of SCA patients with a history of overt stroke have been reported to have large-vessel arteriopathy in the anterior circulation territories 9 . Without secondary prevention based on a long-term transfusion program, the recurrence rate after a first ischemic stroke is very high, reaching 67% for a mean observation time of 9 years in Powars study, with 50% of the events occurring within 2 years after the initial event 10 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 These imaging modalities can provide a broad view of patients’ symptoms and can help localize strokes and ischemia; however, they lack critical histology-grade information that can lead to a better understanding of the underlying mechanisms of blood cell adhesion, stroke, and more. 5 10 Recently, optical imaging methods have been employed; these methods have the advantage of providing higher spatial resolution to view these tissue structures in greater detail. Studies have used fluorescence-based methods to study, for instance, the interactions between brain endothelial cells and RBCs exposed to oxidative stress in vitro 11 or to monitor SCD treatments in vivo using a dorsal skin-fold window chamber model.…”
Section: Introductionmentioning
confidence: 99%